Current progress of PM-localized protein functions in jasmonate pathway. (3rd June 2021) - Qi, Xueying; Gu, Pan; Shan, Xiaoyi
ABSTRACT: Jasmonate (JA), a class of lipid-derived phytohormone, regulates diverse developmental processes and responses to abiotic or biotic stresses. The biosynthesis and signaling of JA mainly occur in various organelles, except for the plasma membrane (PM). Recently, several PM proteins have been reported to be associated with the JA pathway. This mini-review summarized the recent progress on the functional role of PM-localized proteins involved in JA transportation, JA-related defense responses, and JA-regulated endocytosis.